2D computational investigation into transport phenomena of subcooled and saturated flow boiling in large length to diameter ratio micro-channel heat sinks. (February 2022) - Yeo, Ilhwan; Lee, Seunghyun
Highlights: 2D CFD model was developed for coexisting subcooled and saturated flow boiling in micro-channel heat sinks. 2D CFD model was first applied to the annular flow under asymmetric heating conditions. Reasonable accuracy accounting for flow boiling in normal operating conditions was achieved. Accuracy is compromised in annular flow regime as absence of flow redistribution. Abstract: This study computationally investigates into the transport phenomena and heat transfer mechanisms associated with subcooled and saturated flow boiling of R-134a in large length to diameter micro-channel heat sinks. A two-dimensional computational model has been developed for analysis of the interfacial behavior of flow boiling that widely changes from bubbly to annular flow in micro-channel. OpenFOAM based 2D CFD solver was developed by using the volume of fluid method and Lee phase change model, enabling nucleate boiling occurs within the single-phase flow, to solve the transport equation for interface tracking. The conjugate heat transfer at the solid and liquid interface has been considered for the channel wall temperatures, which were compared with experimental results for assessing accuracy of developed CFD model. The high-speed images of flow boiling at multiple locations along the micro-channel were compared with flow patterns acquired from the computational simulation and showed an overall good agreement, which is verified by comparing with the void fractions estimated by the empirical correlations. The measured experimental data were also compared with the simulation results and showed good agreement for limited cases those without dry-out occurrence. The accuracy of two-dimensional CFD simulation in predicting the annular flow under asymmetric heating condition is compromised by excluding the flow along the sidewall which redistributes the flow in circumferential direction. The nonuniform film evaporation at the top and bottom side of the channel precipitates the pseudo dry-out leading to unexpected temperature rise and erroneous thermal responses. In spite of the successful simulation of coexisting subcooled and saturated flow boiling for limited cases without dry-out, this study unveils the causes and mechanisms that limit accurate 2D CFD simulation for widely varying two-phase flow in micro-channel heat sinks.